La afectividad en el hogar y el rendimiento escolar en los niños y niñas del primer año de educación general básica de la escuela fiscal mixta Óscar Efrén Reyes del cantón el Guabo de la provincia de El Oro, período lectivo 2012-2013. - Guanuche Aguilar, Ana Maritza (2013)
In this project I highlighted the psychological and emotional impact that effective deficiency in Children, Reason occur argument why socio affective strategies to develop between humans activities. The operational investigative tour starts with the object of study, cite duly Seleccionada which is helped by a construction theme: affectivity in the Home and School Performance in Children primer Year of Education General Basic of mixed School prosecutor Oscar Efren Reyes of El Guabo canton Province Gold Teaching period 201-2013.